Hazard Identification Risk Assessment and Determining Control (HIRADC) pada Proyek Pembangunan Gedung Rumah Sakit Orthopedi dan Traumatologi di Surabaya - Saidah, Tsaniyatus (Universitas Negeri Surabaya, 2023)
The development of science and technology in the use of modern production tools and materials continues to increase. This aims to improve and facilitate continuity in the production process. However, in addition to the positive side, several scientific and technological developments that occur can trigger an increase in risky sources of danger if not matched by competent human resources so that they can cause work accidents. Factors that influence work accidents include human consequences, work environment, equipment and materials used, and natural factors. This study uses the Hazard Identification Risk Assessment and Determining Control (HIRADC) method. The processed data was obtained from the results of literature studies, observations, interviews, and questionnaires on the Orthopedic and Traumatology hospital building construction project in Surabaya. The results obtained from the results of risk identification based on the variables are human variables there are 25 risks, equipment variables there are 7 risks, and material variables there are 6 risks. Based on the risk assessment that the main factors that may allow the occurrence of risk Most of the human consequences of 66%. Risk control that can be carried out includes: conducting safety induction for new workers, conducting safety briefings, providing first aid kits, workers are required to use personal protective equipment (PPE) according to standards, conducting supervision during activities, carrying out safety patrols on the completeness of personal protective equipment for each worker, providing K3 signs (safety signs) as needed, and carrying out periodic and routine inspections of equipment.